Bone marrow hypocellularity does not affect tolerance or efficacy of azacitidine in patients with higher‐risk myelodysplastic syndromes. (28th January 2014) - Seymour, John F.; Bennett, John M.; List, Alan F.; Mufti, Ghulam J.; Gore, Steven D.; Fenaux, Pierre; Santini, Valeria; Hetzer, Joel; Songer, Stephen; Skikne, Barry S.; Beach, Charles L.
Summary The efficacy and tolerance of azacitidine in higher‐risk myelodysplasia with hypocellular bone marrow (BM) are unknown. This post hoc AZA‐001 trial analysis assessed whether baseline BM cellularity affected the overall survival (OS) advantage demonstrated with azacitidine versus conventional care regimens (CCR). Baseline BM biopsies of <30% cellularity were considered hypocellular with data evaluable from 299 patients (azacitidine n = 154, CCR n = 145); 13% (n = 39) hypocellular, 87% (n = 260) non‐hypocellular. Patient characteristics were balanced between cellularity and treatment groups. Most patients (90–100%) had 2–3 cytopenias at baseline. Median (range) azacitidine treatment cycle lengths were 35·5 (28–54) and 33·0 (15–75) d in hypocellular and non‐hypocellular groups, respectively. At 33 months, median OS was not reached (NR) [95% confidence interval (CI): 19·2, NR] in hypocellular patients receiving azacitidine versus 16·9 months (95% CI: 11·1, 19·3) with CCR (P = 0·001); and in non‐hypocellular patients, it was 21·1 months (95% CI: 16·2, 34·7) versus 15·3 months (95% CI: 9·3, 17·6) (P = 0·012). Azacitidine tolerance was similar regardless of cellularity. Grade 3–4 thrombocytopenia and neutropenia occurred similarly in hypocellular patients treated with azacitidine versus CCR (80% vs. 92% and 88% vs. 75%). Azacitidine OS results are consistent with those from AZA‐001, regardless of cellularity, and demonstrate its safety and efficacy in higher‐risk myelodysplasia with hypocellular BM.